2023
DOI: 10.3389/fphys.2023.1085871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracranial pressure on photoplethysmographic waveform in different cerebral perfusion territories: A computational study

Abstract: Background: Intracranial photoplethysmography (PPG) signals can be measured from extracranial sites using wearable sensors and may enable long-term non-invasive monitoring of intracranial pressure (ICP). However, it is still unknown if ICP changes can lead to waveform changes in intracranial PPG signals.Aim: To investigate the effect of ICP changes on the waveform of intracranial PPG signals of different cerebral perfusion territories.Methods: Based on lump-parameter Windkessel models, we developed a computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The benefits of this device include noninvasive means of measuring ICP and quick triage of patients presenting with acute conditions that may cause elevated ICP, such as trauma. Furthermore, the PPG device is sensitive to environmental factors such as ambient light, noise, and patient specific physiologic parameters, including body size and position, which may affect its reliability [ 19 , 20 ]. For example, the device relies on the arterial pressure to assess ICP; in certain pathologies such as subarachnoid hemorrhage (SAH) with sequela such as vasospasm, cerebral arterial compression may be a distinct physiological process not accurately reflecting ICPs due to disturbance in autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of this device include noninvasive means of measuring ICP and quick triage of patients presenting with acute conditions that may cause elevated ICP, such as trauma. Furthermore, the PPG device is sensitive to environmental factors such as ambient light, noise, and patient specific physiologic parameters, including body size and position, which may affect its reliability [ 19 , 20 ]. For example, the device relies on the arterial pressure to assess ICP; in certain pathologies such as subarachnoid hemorrhage (SAH) with sequela such as vasospasm, cerebral arterial compression may be a distinct physiological process not accurately reflecting ICPs due to disturbance in autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke can arise from multiple mechanisms wherein the local hemodynamic environment plays a pivotal role in embolism [ 38 ]. The transport of cardiogenic plaque (i.e., ‘red’ thrombi) depends on the mechanical properties of the cardio-cerebrovascular system [ 39 ]. Thus, future studies could simulate the cardio-cerebrovascular system by using low-dimensional models to obtain more reliable estimates on the risk of embolism and stroke.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous research suggested that ICP is regulated by the vascular system, and signatures in electrical, blood pressure, and blood oxygenation waveforms have been associated with intracranial events [10]- [12]. Cerebral autoregulation may be impaired when ICP is elevated, leading to changes in blood flow, vasoreactivity, and oxygenation.…”
Section: Introductionmentioning
confidence: 99%